A comparison of two cleaning methods applied in a small animal hospital - Todd Alsing-Johansson; Elin Torstensson; Karin Bergström; Susanna Sternberg-Lewerin; Anna Bergh; Johanna Penell (BMC Veterinary Research)
Abstract Background Environmental cleaning of near-patient surfaces in animal healthcare is an important infection prevention and control measure to lower the risk of spread of healthcare-associated infections (HAIs). There is a lack of reports on the effect of cleaning of near-patient surfaces in animal hospital wards. The aims of this study were to (1) determine bacterial load before cleaning, on near-patient surfaces in dog cages in a mixed medical and surgical ward and investigate factors associated with this bacterial load (2) compare the bacterial reduction on these surfaces after cleaning with (a) a scrubbing brush with detergent and rinsing before and after cleaning, and (b) a microfibre mop moistened with water, and after disinfection carried out after each cleaning method. In each cage the floor and the wall were sampled before cleaning, after cleaning, and after disinfection. Bacterial load and reduction were log10-transformed and for comparisons t-test, one-way Anova and Wilcoxon rank sum test were used. A generalized additive model was performed for analysis of the association between factors and bacterial load. Results The bacterial load in dog cages before cleaning varied, higher loads were noted after longer stay in the cage. The bacterial reduction was in most cases more effective after cleaning with scrubbing brushes with detergent compared to cleaning with damp microfibre mops. After cleaning, a majority of the samples were below the suggested threshold value 2.5 CFU/cm2, except for floor samples after microfibre cleaning. No significant difference in bacterial load, between cleaning methods was noted after disinfection. Overall, the bacterial load was significantly lower on walls than on floors. Conclusions Overall, the bacterial load was below the suggested threshold value after decontamination, except after microfibre cleaning of the floor. Scrub cleaning with a detergent should be considered for cleaning of anti-slip surfaces like the cage floor. The study shows a need for evidence-based cleaning and disinfection routines for near-patient surfaces and evidence-based threshold values for bacterial load, to reduce the risk of HAIs.